Pengaruh Ekspor dan Nilai Tukar Rupiah Terhadap Cadangan Devisa Negara Periode 2012-2022 - sari, Putri wulan; khafiah, Lastri (Ekopem: Jurnal Ekonomi Pembangunan, 2024)
This research aims to analyze the influence of exports and the rupiah exchange rate on the country's foreign exchange reserves in 2012-2022. The independent variables are exports and the rupiah exchange rate, and the dependent variable is foreign exchange reserves. This research uses secondary data in the form of a time series, namely a 11 year time series, namely from 2012-2022. Data obtained from BPS Indonesia, and BI. The research method is quantitative with data analysis used by researchers, namely classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression and statistical tests (coefficient of determination test (R2), t test and F test) with using eviews-10. The results of the partial regression coefficient (t test) show that exports have no effect on the country's foreign exchange reserves, while the rupiah exchange rate has a significant effect on the country's foreign exchange reserves. The results of the F test analysis show that there is a joint and significant influence of the two independent variables, namely exports and the rupiah exchange rate, on the dependent variable, namely the country's foreign exchange reserves